Downregulation of inflammatory cytokines by berberine attenuates Riemerella anatipestifer infection in ducks. (December 2017) - Fernandez, Cherry P.; Afrin, Fahmida; Flores, Rochelle A.; Kim, Woo H.; Jeong, Jipseol; Kim, Suk; Chang, Hong H.; Lillehoj, Hyun S.; Min, Wongi
Abstract: Riemerella anatipestifer, an important infectious bacterium affecting the duck industry, has 5–75% mortality, depending on strain virulence. We previously demonstrated that proinflammatory cytokines are involved in inflammation during, and regulating susceptibility to, R. anatipestifer infection. We investigated the effects of the anti-inflammatory compound berberine in duck splenic lymphocytes stimulated with killed R. anatipestifer, and in R. anatipestifer- infected ducks. IL-17A, IL-17F, and IL-1β transcripts were downregulated, and IFN-γ and IL-10 transcripts enhanced, in berberine-treated stimulated splenic lymphocytes, compared to stimulated untreated splenic lymphocytes. Similarly, IL-17A, IL-17F, IL-6, and IL-1β expressions were significantly reduced, and IFN-γ and IL-10 expressions significantly upregulated, in spleens and livers of R. anatipestifer- infected berberine-treated ducks, compared to infected untreated birds. Moreover, infected and treated birds showed increased survival rates and significantly decreased bacterial burdens compared to infected untreated birds, confirming that inflammatory cytokines are strongly associated with R. anatipestifer infection in ducks. Highlights: R. anatipestifer infection is ameliorated by inflammatory cytokine suppression. Expression levels of IL-17A, IL-17F, IL-1β or IL-6 mRNA were significantly reduced by berberine treatment. Expression of anti-inflammatory cytokine IL-10 was enhanced in vitro and in vivo. Berberine-treated infected ducks had lower mortality rate and bacterial load.